A Real-Time Power Quality Disturbance Detection System Based On The Wavelet Transform - Eristi, Belkis; Yildirim, Ozal; Eristi, Huseyin; Demir, Yakup (Ieee, 2016)
Disturbances occurring on voltage signals following switching events or faults on power systems are defined as power quality problem. Power quality problems result in significant financial losses in the power systems in addition to faulty operation or breakdown of sensitive loads connected to the power system. Therefore, power quality problems should be swiftly detected and eliminated. This paper proposes a real-time embedded detection system for the purpose of identification of power quality disturbances. The detection system developed has been created using the wavelet transform in the Field Programmable Gate Array (FPGA) media. The general structure of FPGA-based detection system comprises two fundamental parts: hardware and software. Hardware structure comprises signal input card, FPGA and computer components. The software stage includes FPGA and graphical interface software. An experimental setup of the power system has been created in laboratory environment in order to test the FPGA-based detection system, determine accuracy rates and assess its success. Various power quality disturbances have been created over this model in wide parameter intervals. When the results obtained for the real-time power quality disturbance detection system developed under this study are examined, it has been seen that hardware and software designs are quite effective, fast and of high achievement performance.
51st International Universities Power Engineering Conference (UPEC) -- SEP 06-09, 2016 -- Coimbra Inst Engn, Coimbra, PORTUGAL
Keywords: Power quality disturbance; Feature extraction; Wavelet transform; Embedded systems; Detection system